2021
DOI: 10.1080/22221751.2021.1931465
|View full text |Cite
|
Sign up to set email alerts
|

Mining of linear B cell epitopes of SARS-CoV-2 ORF8 protein from COVID-19 patients

Abstract: The landscape of linear B cell epitopes of SARS-CoV-2 ORF8 protein is determined by analysing serum IgG response of COVID-19 patients ABSTRACT Given the ongoing SARS-CoV-2 pandemic, identification of immunogenic targets against the viral protein will provide crucial advances towards the development of sensitive diagnostic tools and vaccination strategies. Our previous study has found that ORF8 protein of SARS-CoV-2 is highly immunogenic and shows high sensitivity in identifying COVID-19 disease.In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Many studies have been performed to identify B-cell linear epitopes in the SARS-CoV-2 proteins [18,19,[26][27][28][29][30][31][32][33][34][35][36][37]. Our study confirms previous findings, identifying the same overall regions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many studies have been performed to identify B-cell linear epitopes in the SARS-CoV-2 proteins [18,19,[26][27][28][29][30][31][32][33][34][35][36][37]. Our study confirms previous findings, identifying the same overall regions.…”
Section: Discussionsupporting
confidence: 90%
“…These epitopes are important for diagnosis, for the development of monoclonal antibodies for prevention and treatment, and for the design of peptide-based vaccines [14][15][16]. Several immunodominant linear epitopes have been identified on the S, M, E, N (for review [17]) and ORF8 [18] proteins. However, only a few studies have investigated the possible correlation between specific reactivity to particular linear epitopes and disease severity [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that antibodies and peptides against ORF8 are readily detected in the sera of COVID-19 patients ( 25 , 26 ), suggesting that ORF8 is a secreted viral protein with highly immunogenic properties ( 29 ). We found that ORF8 was readily detected in lung bronchial epithelial cells of SARS-CoV-2-infected ferrets and mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SARS-CoV-2 ORF8 consists of 121 amino acids, including an N-terminal signal peptide (1 to 15 aa) and a C-terminal immunoglobulin (Ig)-like domain (16 to 121 aa). It has been identified as a secreted, highly immunogenic, and rapidly evolving protein ( 24 26 ). Sequence alignment shows that the SARS-CoV-2 ORF8 shares high similarity with Bat-RaTG13-CoV ORF8 (95%) but low similarity with SARS-CoV ORF8 (30%), suggesting that SARS-CoV-2 ORF8 may have originated from the Bat-RaTG13-CoV ORF8 ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, most developed or under developing vaccines have focused on virus surface proteins such as spike and nucleocapsid protein. These proteins show good immunity, but some studies have indicated the high immunogenicity of the ORF8 protein [19]. Also, the ORF7b and ORF10 proteins are unique, and they lacked any sequence homology with other viral proteins [20].…”
Section: Introductionmentioning
confidence: 99%